1978
DOI: 10.1111/j.1365-2605.1978.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Epididymal Sperm Motility; An Approach to Male Fertility Regulation

Abstract: Thermal immobilization was designed as a simple approach to study factors controlling sperm motility. Heating dissected epididymis or isolated epididymal sperm at 48°C to 52°C for 5 min abruptly and completely immobilized the sperm. The thermally immobilized sperm showed some alteration of membrane lipids, as indicated by the response of the surface ATPase to temperature change. However, no qualitative change in the surface negative charge was detectable by the binding of the cells to DEAE‐Sephadex beads. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…plaque-forming assay (Kennedy & Axelrod 1971) and isolation of plasma membrane (Jacobson et al 1974;Jacobson 1977;Jacobson & Branton 1977;Jacobson et al 1978;Kalish et al 1978). Since sperm tails are highly negatively charged (Nevo et al 1961;Bedford 1963;Yanagimachi et al 1972), we have demonstrated the strong binding between rat epididymal spermatozoa and positive beads, diethylaminoethyl (DEAE)-Sephadex (Chulavatnatol et al 1978). This paper describes further study on the binding and our attempt to apply the spermatozoa-bead interaction as a simple and inexpensive mean to isolate heads and tails of rat epididymal spermatozoa.…”
mentioning
confidence: 64%
“…plaque-forming assay (Kennedy & Axelrod 1971) and isolation of plasma membrane (Jacobson et al 1974;Jacobson 1977;Jacobson & Branton 1977;Jacobson et al 1978;Kalish et al 1978). Since sperm tails are highly negatively charged (Nevo et al 1961;Bedford 1963;Yanagimachi et al 1972), we have demonstrated the strong binding between rat epididymal spermatozoa and positive beads, diethylaminoethyl (DEAE)-Sephadex (Chulavatnatol et al 1978). This paper describes further study on the binding and our attempt to apply the spermatozoa-bead interaction as a simple and inexpensive mean to isolate heads and tails of rat epididymal spermatozoa.…”
mentioning
confidence: 64%
“…Methods used included whole cell microelectrophoresis (Bedford 1963;Lopez et al 1987;Nevo et al 1961), isoelectric focusing (Moore 1979), labelling with tritiated polycationised ferritin followed by scintillation counts (Toowicharanont and Chulavatnatol 1983), binding of charged beads (Chulavatnatol et al 1978) and visualisation of anionic sites in transmission electron microscopy (TEM) after direct labelling with cationic probes such as colloidal iron hydroxide, ruthenium red and cationised ferritin (Danon et al 1972;Delgado et al 1990;Fléchon 1975;Lopez et al 1987;Yanagimachi et al 1972). As concluded from electrophoretic mobility and qualitative judgment of sperm labelling density in TEM, spermatozoa were thought to successively acquire acidic groups as they migrate through the epididymis (Bedford 1963;Lopez et al 1987;Toowicharanont and Chulavatnatol 1983).…”
Section: Introductionmentioning
confidence: 99%